Coalescence‐induced jumping of microdroplets on superhydrophobic surfaces—A numerical study. (25th August 2022) - Konstantinidis, Konstantinos; Göhl, Johan; Mark, Andreas; Sasic, Srdjan
Abstract: We develop a numerical framework for simulating the coalescence and jumping of microdroplets on superhydrophobic surfaces. The framework combines the volume of fluid (VOF) method with models for advancing and receding contact angles on a number of superhydrophobic surfaces. We demonstrate the temporal and spatial convergence of the framework and show agreement between our numerical results and other experimental studies. The capillary‐inertial scaling is investigated together with the existence of a cut‐off behaviour frequently observed in the lower size‐range of that regime. We investigate findings in some of the previous studies that the cut‐off behaviour can be attributed to viscosity effects and dissipation due to interaction with surface microstructures. We exemplify specific features related to the jumping process and the corresponding energy budget analysis when microdroplets coalesce and jump. We have tested droplets of a radius as small as 0.5 μm that are still jumping but recorded a decrease in the jumping velocity and the degree of energy conversion compared to the jumping of larger droplets. We argue and prove that strong capillary forces originating from the high curvature oscillations dissipate the energy of the system significantly faster in the case of microdroplets.